Catch me iIf you can : education and catch-up in the industrial revolution - Sascha O. Becker; Erik Hornung; Ludger Woessmann (Center for Economic Studies and ifo Institute (CESifo), 2009)
Existing evidence, mostly from British textile industries, rejects the importance of formal education for the Industrial Revolution. We provide new evidence from Prussia, a technological follower, where early-19th-century institutional reforms created the conditions to adopt the exogenously emerging new technologies. Our unique school-enrollment and factory-employment database links 334 counties from pre-industrial 1816 to two industrial phases in 1849 and 1882. Controlling extensively for pre-industrial development, we use pre-industrial education as an instrument to identify variation in later education that is exogenous to industrialization itself. We find that basic education significantly accelerated non-textile industrialization in both phases of the Industrial Revolution.
Keywords: N13; N33; I20; O14; 330; human capital; industrialization; Prussian economic history; Bildungspolitik; Allgemeinbildung; Bildungsinvestition; Industrialisierung; Entwicklungskonvergenz; Wirtschaftsgeschichte; Preußen